Effects of CaO2 based Fenton - like reaction on heavy metals and microbial community during co-composting of straw and sediment. (August 2022) - Chen, Yaoning; Luo, Xinli; Li, Yuanping; Liu, Yihuan; Chen, Li; Jiang, Hongjuan; Chen, Yanrong; Qin, Xiaoli; Tang, Ping; Yan, Haoqin
Abstract: In this study, a Fenton-like system was constructed by CaO2 and nano-Fe3 O4 in the co-composting system of straw and sediment. Its effect on the passivation of heavy metals and the evolution of microbial community were investigated. The results showed that the establishment of CaO2 -Fenton-like system increased the residual Cu and residual Zn by 27.62% and 16.80%, respectively. In addition, the CaO2 -Fenton-like system facilitated the formation of humic acid (HA) up to 20.84 g·kg −1 . Redundancy analysis (RDA) showed that the CaO2 -Fenton-like system accelerated bacterial community succession and promoted the passivation of Cu and Zn. Structural equation models (SEMs) indicated that Fenton reaction affected Cu and Zn passivation by affecting pH, bacterial communities, and HA. This study shows that the CaO2 -Fenton-like system could promote the application of composting in the remediation of heavy metals contamination in sediment. Graphical abstract: Image 1 Highlights: CaO2 -Fenton-like system has been successfully established in composting. CaO2 -Fenton-like system could accelerate the bacterial evolution and promote the formation of humic acid. The passivation of heavy metals was enhanced. Fenton reaction could promote the remediation of Zn and Cu by alter environmental factors and bacterial community.